Sarcoidosis and Sarcoid-Like Reaction Associated with Pancreatic Malignancy: Are You Able to Read a Riddle? - Mastroroberto, Marianna; Berardi, Sonia; Fraticelli, Lucilla; Pianta, Paolo; Ercolani, Giorgio; Cancellieri, Alessandra; Sama, Claudia (JOP. Journal of the Pancreas, 2012)
Context The sarcoidosis is an idiopathic multisystem inflammatory disease characterized by the presence of non-caseating granulomas in the affected organs. The clinical picture includes non-specific systemic symptoms and organ-specific symptoms, but it is frequently asymptomatic. Although not fully understood, a clear association between sarcoidosis and malignancies has been reported. In neoplastic patient, beside classical sarcoidosis, cases of sarcoid-like reaction have been extensively described, a condition characterized by the presence of non-caseating granulomas in the lymph nodes draining the tumor or, less commonly, in the distant lymph nodes; this is considered a benign non progressive condition, potentially regressive following neoplasm eradication. Case report We report the first case of sarcoidosis/sarcoid-like reaction associated with neuroendocrine tumors of the pancreas. Conclusion This clinical case highlights the difficulty and importance of differential diagnosis of lymphadenopathy in the management of neoplastic disease, and in view of the evolving clinical picture, if a distinction between sarcoidosis and sarcoid-like reaction is a clinical reality or if they is just represent different stage of the same disease. Therefore, we believe that a follow-up is necessary even in case of sarcoid-like reaction, since no data are reported in the literature on the long-term of this condition once treated the associated tumor. Image: Diff Quik® stain for rapid-on-site-examination.